Experimental Study on Fine Particulate Matter Removal Efficiency and the Emission Characteristics of WESP under Different Loads - Xipu LIU; Dongyang LI; Chao ZHANG (Zhongguo dianli)
In this paper, the dust mass concentrations and emission characteristics are tested using ELPI+ device at the inlet and outlet of a wet electric-static precipitator (WESP) under six different conditions, i.e., the combination of the boiler load at 100%, 75%, and 50%, with the WESP operated at high power and optimized energy-saving modes, respectively. From the experimental results, under 100% load and WESP energy-saving operation mode, significant increases are observed in the concentration of total dust emission, PM10 and PM2.5. Particularly, the total dust emission mass concentrations have even exceeded 5 mg/m3. However, under medium or low loads with WESP energy-saving operation mode, the total dust emission concentration still increases significantly, while the concentrations of PM10 and PM2.5 do not change much. The smaller the particle size, the less change of concentrations is noticed. Therefore, the energy-saving optimization test can provide technical assistance for the optimized unit operation mode with the goal of ultra-low emission also achieved at the same time. Additionally, PM10 and PM2.5 have little influence on the total dust emission under medium or low loads. The fly ash particles at the inlet and outlet of the WESP demonstrate the pattern of typical bimodal distribution. Under low or medium loads, the mass of the particles of 2~10 μm accounts for about 30% of all PM10 particle mass if the WESP operates at high power mode, while that percentage jumps to 50% if it operates at energy-saving mode.